2006
DOI: 10.1891/194589506787382422
|View full text |Cite
|
Sign up to set email alerts
|

Parenting (Parental Attitude), Child Development, and Modalities of Parent-Child Interactions: Sayings, Proverbs, and Maxims of Ethiopian Jews in Israel

Abstract: The author presents and discusses typical (traditional) modalities of parent-child interaction based on proverbs, sayings and maxims, and on participant observation, informal talks, and personal experience working with Ethiopian Jews in Israel. Although the author’s assumptions are clear that there is no direct causal link between a single proverb/saying and the behavior associated with it, he also assumes that all the tens of sayings presented combined with the relevant ethnographic data may reveal some patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Some of the challenges reported in this study were partially reported by the previous Ethiopian CST study and not at all by studies from other settings, such as the lack of toys in the homes ( Salomone et al, 2022 ; Tekola, Girma, et al, 2020 ). Ethiopian children play with ordinary objects found within their household environment ( Berhanu, 2006 ), rather than with toys. The initial adaptation to the Ethiopian context (outlined in the study by Tekola, Girma, et al, 2020 ) already included more emphasis on household items and items in the environment such as sticks and leaves than the original WHO CST materials.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the challenges reported in this study were partially reported by the previous Ethiopian CST study and not at all by studies from other settings, such as the lack of toys in the homes ( Salomone et al, 2022 ; Tekola, Girma, et al, 2020 ). Ethiopian children play with ordinary objects found within their household environment ( Berhanu, 2006 ), rather than with toys. The initial adaptation to the Ethiopian context (outlined in the study by Tekola, Girma, et al, 2020 ) already included more emphasis on household items and items in the environment such as sticks and leaves than the original WHO CST materials.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, proverbs and sayings are mainly considered as elements of language, in which the peculiarities of thinking, the cultural experience and the system of values of a particular society are presented in a concentrated form (Orlova et al, 2018). Such an approach makes it possible to identify and analyze the underlying concepts based on the material under study: a) spatial concepts: the basics of the world order (Taukebaeva et al, 2014), natural and climatic conditions of life (Baran, 2016), concepts of "motherland" and "home" (Gasparjan, 2018); b) temporary concepts: calendar and linear time (Utkina & Kovalevich, 2018); c) anthropological concepts: sensual perception of the world around us -colour (Mosiashvili, 2015), taste (Ionescu, 2017) and other human preferences, social roles -parents and their children (Berhanu, 2006), spouses (Sevriuk, 2018), neighbours (Pintin Go, 2018), labour activity (Lysenko, 2018) and commodity-money relations (Zharkova, 2014), emotions and feelings (Shkurko, 2014), a system of values (Glukhova et al, 2015), and many others. A number of studies touch upon the issue of borrowings and influences (Iakovleva & Nikolaeva, 2016), as well as offer a comparative-contrastive analysis of proverbs and sayings in, as a rule, two unrelated languages (Ionescu, 2017;Mosiashvili, 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%